La ricezione di Seneca tragico tra Quattrocento e Cinquecento Edizioni e volgarizzamenti - Capirossi, Arianna (Premio Ricerca «Città di Firenze», 2020)
The volume investigates the reception of Senecan tragedies during Humanism, focusing on printed editions and on translations in Florentine vernacular language. The first chapter summarizes the manuscript transmission of the tragedies up to the first age of printing, with a glimpse to their possible theatrical representations. The second chapter contains the description of the printed editions from the princeps (before 1478) to the three-comment edition by Josse Bade (1514): I analysed the main paratexts, with a focus on the commentaries by Gellio Bernardino Marmitta, Daniele Caetani, and Josse Bade, and reconstructed the identities of the personalities who contributed to the publication of the tragedies. The third chapter offers a stylistic study of the five vernacular translations produced up to the year 1498. In the volume I publish the translations by Evangelista Fossa (Agamennone) and Pizio da Montevarchi (Hercule furent and Hyppolito), which lacked a modern edition.